1979
DOI: 10.1093/ajcn/32.11.2301
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in the mineral content of human milk

Abstract: Thirty-eight lactating women, from 1 to 31 months postpartum, provided monthly milk samples for determination of calcium, magnesium, manganese, copper, iron, and zinc. Subjects remained in the study an average of 4 consecutive months, with a maximum participation of 9 months. Subject variation accounted for the majority of variance in the raw data. After statistically controlling subject effect, copper, iron, and zinc levels were shown to be significantly related to duration of lactation. Prediction equations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(84 citation statements)
references
References 27 publications
12
71
1
Order By: Relevance
“…Iron intakes of our study participants were observed to be less than their requirements; however, it was not found to be related to the breast milk concentration. Their breast milk iron concentration was found to be similar to values for American lactating mothers with higher iron intakes; 0.42 mg/L and 47.1 mg/d among women at 7 to 9 mo postpartum, while 0.38 mg/L and 40.8 mg/d among women at 10 to 12 mo postpartum, respectively (31).…”
Section: Discussionmentioning
confidence: 59%
“…Iron intakes of our study participants were observed to be less than their requirements; however, it was not found to be related to the breast milk concentration. Their breast milk iron concentration was found to be similar to values for American lactating mothers with higher iron intakes; 0.42 mg/L and 47.1 mg/d among women at 7 to 9 mo postpartum, while 0.38 mg/L and 40.8 mg/d among women at 10 to 12 mo postpartum, respectively (31).…”
Section: Discussionmentioning
confidence: 59%
“…Human milk is generally low in Mn content (1.8-27.5 μg/L); however, Mn concentrations in infant formulas can vary dramatically (33-300 μg/L) (Keen and Zidenberg-Cherr, 1994;Murthy et al, 1971;Stastny et al, 1984;Vaughan et al, 1979). In human (and animal) milk Mn concentrations are associated with the stage of lactation Stastny et al, 1984;Vaughan et al, 1979;Krachler and Rossipal, 2000; Table 1).…”
Section: Milk and Infant Formulasmentioning
confidence: 99%
“…In human (and animal) milk Mn concentrations are associated with the stage of lactation Stastny et al, 1984;Vaughan et al, 1979;Krachler and Rossipal, 2000; Table 1). For example Stastny and coworkers (1984) reported that mean (± SD) human milk Mn concentrations in the fourth week of lactation were 6.6 ± 4.7 μg/L and these levels were significantly higher than those collected during the 12 th week of lactation (3.5 ± 1.4 μg/L).…”
Section: Milk and Infant Formulasmentioning
confidence: 99%
“…14,15 The age of the child is an important consideration in assessing the adequacy of complementary feeding practices. [16][17][18] Eruption of teeth influences when to introduce complementary feeding, but the process typically leads to a loss of appetite which affects food intake. Secondary analysis of Demographic and Health Surveys in Ethiopia conducted by Melkam et al 19 and in Nepal by Khana et al 20 indicated that as children grow older their diets typically become more diverse.…”
Section: Introductionmentioning
confidence: 99%